The Effect of Cell Salvage on Bleeding and Transfusion Needs in Cardiac Surgery. (1st September 2022) - Tachias, Frixos; Samara, Evangelia; Petrou, Anastasios; Karakosta, Agathi; Siminelakis, Stavros; Apostolakis, Efstratios; Tzimas, Petros
Abstract : Introduction . Cell salvaging is well established in the blood management of cardiac patients, but there remain some concerns about its effects on perioperative bleeding and transfusion variables. This randomized controlled study investigated the potential effects of the centrifuged end-product on bleeding, transfusion rates, and other transfusion-related variables in adult cardiac surgery patients submitted to extracorporeal circulation. Materials and Methods . Patients were randomly chosen to receive (cell-salvage group, 99 patients) or not to receive (control group, 110 patients) the centrifuged product of a cell salvage apparatus. Bleeding and transfusion rates according to the universal definition of perioperative bleeding (UDPB) classification, postoperative hemoglobin, coagulation, and oxygenation indices were recorded and compared between the groups. Results . Both groups had almost identical bleeding and transfusion rates (median value: 2 units of red blood cells (RBC) and no units of fresh frozen plasma (FFP) and platelets (PLT) for both groups, p > 0.05 ). Patients in the cell-salvage group presented slightly higher hemoglobin concentrations (10.6 ± 1.1 vs. 10.1 ± 1.7 g/dL, p < 0.05, respectively) and a tendency towards better oxygenation indices (Pa O2 /Fi O2 : 241 ± 94 vs. 207 ± 84, p = 0.013 ) in the postoperative period albeit with a tendency for prolongation of prothrombin time (INR: 1.31 ± 0.18 vs. 1.26 ± 0.12, p = 0.008 ). Conclusion . Within the study's constraints, the perioperative use of the cell salvage concentrate does not seem to affect bleeding or transfusion variables, although it could probably ameliorate postoperative oxygenation in adult cardiac surgery patients. A tendency to promote coagulation disturbances was detected.